Efficacy and safety of clomiphene citrate therapy in patients with male idiopathic infertility: A systematic review - Enriquez Gutierrez, Gianfranco Fabricio (2021)
Introduction: Male idiopathic infertility is a rising problem globally and a significant challenge in clinical practice. Clomiphene citrate emerges as a promising therapy. Our objective is to synthesize available primary evidence about the efficacy and safety of clomiphene citrate treatment for male idiopathic infertility. Materials and Methods: We carried out a Systematic Review. We performed the primary search in PubMed/MEDLINE, Embase, WoS, Medline, Scopus, Cochrane and Trip Database until December 2020 for RCTs evaluating the effect of clomiphene citrate therapy compared to placebo and other therapies on adult males from any age group with idiopathic infertility diagnosis according to WHO 2010 criteria and ICD-10. The outcomes we studied were divided between efficacy: pregnancy and spermogram changes; and security: adverse effects. We evaluated the risk of bias using the Cochrane® Risk of Bias tool. Results: From 1010 registries, we selected 11 RCTs. Sample sizes varied between 23 and 141 participants. Five studies compared clomiphene citrate versus placebo and the remaining six compared clomiphene versus other therapies. The clomiphene doses used in the intervention group were 25mg and 50mg. For the main outcome, pregnancy, nine studies presented results, only one had a positive effect with unclear results (Ghanem et al. RR 3,00; 95% CI; 1,09 –8,25; p<0,05). Seven trials reported a significant increase in sperm concentration, three reported increased motility and one in morphology. However, these changes did not reflect on the increase in pregnancies. Six studies reported adverse effects out of 291 patients that received clomiphene citrate. 12 participants (4.12%) reported adverse effects, including headache and visual symptoms, no serious adverse effects were presented. Conclusion: Due to the variability and heterogeneity of the studies, a qualitative synthesis could not be realized. Nevertheless, evidence suggests pregnancy would not be achieved and so, their use in male idiopathic infertility could not be recommended. Furthermore, better quality randomized controlled trials with a larger sample size are required to measure its effect more validly and reliably.